Metabolic versatility of Caldarchaeales from geothermal features of Hawai’i and Chile as revealed by five metagenome-assembled genomes - Balbay, Manolya Gul; Shlafstein, Maximillian D.; Cockell, Charles; Cady, Sherry L.; Prescott, Rebecca D.; Lim, Darlene S. S.; Chain, Patrick S. G.; Donachie, Stuart P.; Decho, Alan W.; Saw, Jimmy H. (Frontiers in Microbiology, 2023)
Members of the archaeal order Caldarchaeales (previously the phylum Aigarchaeota) are poorly sampled and are represented in public databases by relatively few genomes. Additional representative genomes will help resolve their placement among all known members of Archaea and provide insights into their roles in the environment. In this study, we analyzed 16S rRNA gene amplicons belonging to the Caldarchaeales that are available in public databases, which demonstrated that archaea of the order Caldarchaeales are diverse, widespread, and most abundant in geothermal habitats. We also constructed five metagenome-assembled genomes (MAGs) of Caldarchaeales from two geothermal features to investigate their metabolic potential and phylogenomic position in the domain Archaea. Two of the MAGs were assembled from microbial community DNA extracted from fumarolic lava rocks from Mauna Ulu, Hawai'i, and three were assembled from DNA obtained from hot spring sinters from the El Tatio geothermal field in Chile. MAGs from Hawai'i are high quality bins with completeness >95% and contamination <1%, and one likely belongs to a novel species in a new genus recently discovered at a submarine volcano off New Zealand. MAGs from Chile have lower completeness levels ranging from 27% to 70%. Gene content of the MAGs revealed that these members of Caldarchaeales are likely metabolically versatile and exhibit the potential for both chemoorganotrophic and chemolithotrophic lifestyles. The wide array of metabolic capabilities exhibited by these members of Caldarchaeales might help them thrive under diverse harsh environmental conditions. All the MAGs except one from Chile harbor putative prophage regions encoding several auxiliary metabolic genes (AMGs) that may confer a fitness advantage on their Caldarchaeales hosts by increasing their metabolic potential and make them better adapted to new environmental conditions. Phylogenomic analysis of the five MAGs and over three thousand representative archaeal genomes showed the order Caldarchaeales forms a monophyletic group that is sister to the clade comprising the orders Geothermarchaeales (previously Candidatus Geothermarchaeota), Conexivisphaerales and Nitrososphaerales (formerly known as Thaumarchaeota), supporting the status of Caldarchaeales members as a clade distinct from the Thaumarchaeota.